Democratic backsliding through electoral irregularities: The case of Venezuela - Corrales, Javier (European Review of Latin American and Caribbean Studies, 2020)
This article discusses how electoral irregularities contributed to democratic backsliding in Venezuela under chavista rule (1999-2019). It draws from an original database of electoral irregularities created from primary and secondary sources covering a total of 24 electoral contests. I find that Venezuela experienced 117 electoral irregularities during this twenty-year period. Almost every electoral contest exhibited one irregularity, if not more. Electoral irregularities served two goals: to provide double insurance for the ruling party, and to encourage abstentionism (and divisions) across the opposition. They also increased every time the ruling party felt more electorally threatened. The article proposes a typology of irregularities applicable to other cases. It also evaluates how the opposition responded to the rise of irregularities, pointing out strategies that failed and those that worked. Resumen: Retroceso democrático por irregularidades electorales: El caso de Venezuela.Este artículo discute cómo las irregularidades electorales contribuyeron al retroceso democrático en Venezuela bajo gobiernos chavistas (1999-2019). Se fundamenta en una base de datos inédita de irregularidades electorales creada a partir de fuentes primarias y secundarias que cubren un total de 24 procesos electorales. Venezuela cometió 117 irregularidades electorales durante este período de veinte años. En casi todos los procesos electorales hubo al menos una irregularidad. Las irregularidades electorales cumplieron dos objetivos: proporcionar un doble seguro para el partido gobernante y alentar la abstención (y la división) en toda la oposición. También aumentaron cada vez que el partido gobernante se vio más amenazado electoralmente. El artículo propone una tipología de irregularidades aplicables en otros casos. También evalúa cómo respondió la oposición al aumento de las irregularidades, señalando las estrategias que fallaron y las que funcionaron.